ENGLISH COMIC TO IMPROVE STUDENT’S READING SKILL AT SMP NEGERI 3 TONDANO - Vincentia Ester Gusti Br. Tambunan; Nihta V. F. Liando; Tirza Kumayas (Program Studi Pendidikan Bahasa Inggris, 2022)
The reading’s result in this research has function to find out if this comic in reading skill can improve student’s understanding especially, to understand the meaning based on the reading material. Researcher used quantitative method to collect the subject data. Students can read comic with picture, colour, and dialogue that can be more interesting as reading media. At the school researcher start the research with pre-experimental class researcher used pre-test, treatment and post-test to collect the data. The post-test used three types of tests which is comprehension test, play idea questions and inference questions. The subject of this research was grade nine Junior High School at SMP Negeri 3 Tondano, which consisted of 29 students. The data were calculated with the result of students’ pre-test was 51 and the post-test was 85. The different score between pre-test and post-test was 34. The result of this study is indicated that mean score of post-tests was higher 34% more than pre-test. As the result, researcher can conclude that reading comprehension using comic can help students improve their reading skill. This media also can be an effective way that can help student do not feel bored in class with the learning media.